Digital Security Strategies Through Stakeholder Collaboration in Combating Online Gambling from an Organizational Resilience Perspective - Isro' Kurniawan Rahakbauw; Palupi Lindiasari Samputra (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
Online gambling (judol) has become one of the significant challenges in the digital era, causing multidimensional effects, including economic losses, threats to social stability, and weakening of the law. Despite various efforts such as blocking sites and cutting off funding streams, quick adaptation by perpetrators, lack of coordination among agencies, and limitations in technology and human resources remain major obstacles. This study aims to evaluate the performance of stakeholders related to handling online gambling, map the obstacles faced by stakeholders, and formulate strategies for handling online gambling through stakeholder collaboration. The research method used in this study is a qualitative approach with interview techniques with stakeholders, namely Komdigi, Polri, and PPATK, using formal evaluation analysis. The results show that Komdigi's performance is not effective due to resource limitations and technological capacity, POLRI faces obstacles in legal instruments and international cooperation, while PPATK also has resource constraints and secondary data limitations. This study finds that site blocking and cutting off funding streams are effective but hindered by perpetrators' technological adaptation and suboptimal cross-agency coordination. Low public awareness also complicates the handling. Recommendations include strengthening coordination, optimizing detection technology, adaptive regulation, public education, and international cooperation for a more holistic and sustainable approach.